‘When language skews narratives’: Critical medical humanitarianism after Beirut, Paris, and Baghdad (Medicine Anthropology Theory, 2017)
The ISIS-led attacks on Paris, Beirut, and Baghdad in November 2015 were covered in a variety of ways by major news outlets globally. Coverage of the Paris attack was widespread, and layered with personal stories about those personally affected and analysis about the effects of terrorism on the French way of life. By comparison, little coverage was given to either the Beirut or Baghdad events, the experiences of those suffering on the ground, or the wider issue of the effects of terrorism within Lebanese and Iraqi communities. In this think piece, the bombings in Beirut are used as a lens for examining the politics and consequences of mediated silence or ‘forgetting’ of violence and suffering in the Middle East. We employ a critical humanitarianism, rooted in a social medicine analysis, to connect these media trends to the training of health professionals. Our approach helps build accountability for the inequalities present in the Western construction of suffering and the emotive aspects of global violence, and promotes a wider conversation about the long-term biomedical effects of violence.